An Appraisal of the Functioning and Effectiveness of the East African Court of Justice - Possi, Ally (Potchefstroom Electronic Law Journal, 2018)
This contribution reflects on the functioning of the East African Court of Justice (EACJ) and judges its effectiveness by assessing the Court’s role of ensuring adherence to, the application of and compliance with the East African Community (EAC) Treaty. The EACJ became operational on 30 November 2001, following its inauguration after the swearing in of its judges and the Registrar. During this initial stage of the Court’s existence there were indications that the EACJ was failing to stamp its authority on the activities of the Community. The main reason for this failure is the existence of gaps in the EAC Treaty, which prevent the EACJ from effectively discharging its functions. In addition, as shown in this article, the EACJ has been delivering judgements on the grounds of doubtful authority which has gradually diminished the Court’s legitimacy. Given its relevance to the EAC, this may therefore be the time to audit the EACJ’s functioning and reflect on whether it is moving in the right direction. The hypothesis of this article is that the EACJ has been struggling to establish its authority in the region, mostly in the areas of human rights, the rule of law and good governance. In tracing its history so far it is easy to discern its strategic attempts at judicial law-making to arrogate to itself the role of the protector of human rights. While it is acknowledged that the EACJ is increasingly receiving cases of a divergent nature, most of these cases have had little influence on the integration project or are outside the scope of its mandate.